Securitization of migrations and surveillance technologies in Argentina, 1981-2001 - Pereira , Manuel Andrés (2024)
This article analyses the incorporation of new technologies for migration and border surveillance in Argentina (1981-2001). In methodological terms, information was taken from official documents (decrees, contracts, and public tenders), as well as from semi-structured interviews with personnel from the Ministry of the Interior and the National Directorate of Migration. The interventions of specialists and parliamentary experts who participated in the Population and Human Resources Commission of the Chamber of Deputies between 2000 and 2002 were also considered. The findings suggest that the incorporation of new technologies for migration and border control reflect the prevalence of long-term standardised measures related to the processes of securitisation of “border immigration” that would be aimed at protecting the “social order” in Argentina.